Treading the tightrope of femininity: Transforming gendered subjectivity in a therapeutic community. Issue 4 (November 2019) - Perheentupa, Inna; Salmenniemi, Suvi
This article examines the therapeutic self-transformation process in a self-help group in Russia. Drawing on participant observation and interviews, and engaging with debates on therapeutic technologies and the transformation of gender relations, it explores how the self-help group shapes how participants come to understand and act upon themselves. It shows that the process of self-transformation is profoundly gendered, problematising femininity and identifying it as an object of therapeutic intervention. Rather than collectively contesting gendered power and disadvantage, participants are invited to cultivate traditional notions of femininity and masculinity and learn to draw pleasure from them. We argue that this message may be appealing to women because it speaks to their lived experience of exhaustion and precarity, and offers them the prospect of overcoming it through a mythologised heteronormative order. It offers solace and a potential escape route where room for political agency is limited and feminist discourse heavily vilified. Yet the article also shows that participants do not merely internalise the ideological messages of the group, but engage with them in contradictory and ambivalent ways.